Sustainability-as-a-Service: Conceptualizing Value Co-Creation in Evolving Service Ecosystems - Mansouri, Youssef El Mansouri; Zahidi, Amina Zahidi; Boulif, Karim Boulif (ICON Publisher, 2025)
This conceptual paper advances the integration of sustainability and Service-Dominant Logic (S-D Logic) by proposing the notion of